Pesticide responses of Arctic and temperate microalgae differ in relation to ecophysiological characteristics - Du, Juan; Izquierdo, Disney; Naoum, Jonathan; Ohlund, Leanne; Sleno, Lekha; Beisner, Beatrix; Lavaud, Johann; Juneau, Philippe (Aquatic Toxicology, 2022)
International audience